The nation under threat: secularist, racial and populist nativism in the Netherlands - Kešić, Josip; Duyvendak, Jan Willem (Patterns of prejudice, 2019)
Right-wing discourses and issues of belonging and collective identity in Europe's political and public spheres are often analysed in terms of Islamophobia, racism and populism. While acknowledging the value of these concepts, Kešić and Duyvendak argue that these discourses can be better understood through the logic of nativism. Their article opens with a conceptual clarification of nativism, which they define as an intense opposition to an internal minority that is seen as a threat to the nation due to its 'foreignness'. This is followed by the analysis of nativism's three subtypes: secularist nativism, problematizing particularly Islam and Muslims; racial nativism, problematizing black minorities; and populist nativism, problematizing 'native' elites. The authors show that the logic of nativism offers the advantages of both analytical precision and scope. The article focuses on the Dutch case as a specific illustration of a broader European trend.